Metrology Challenges in Quantum Key Distribution. Issue 1 (1st December 2022) - Gui, Y; Unnikrishnan, D; Stanley, M; Fatadin, I
Abstract: The metrology of the QKD devices and systems grows increasingly important in recent years not only because of the needs for conformance and performance testing in the standardization, but more importantly, imperfect implementation of the devices and systems or deviations from the theoretical models, which could be exploited by eavesdropper, should be carefully characterised to avoid the so-called side channel attack. In this paper, we review the recent advances in many aspects of the QKD metrology in both fibre based QKD and free space QKD systems, including a cutting edge metrology facility development and application, traceable calibration methods, and practical device characterising technologies, all of which have been contributed by the metrology communities and relative institutions.